Baisse des taux de profit et d’intérêt en France - Patrick Castex (Revue de la Régulation)
Since 1998 in France, in spite of the relative stagnation of their level, the share of salaries in the added value increased and that of the profits decreased. This decline, multiplied by the reduction of the apparent capital productivity, made the returns on capital fall. To restore them, companies indeed increased their investments: the rise of the organic composition of the capital, accelerated by the speculative rise of the market values of assets, produced a suraccumulation. The third oil crisis, which began in 1999, especially consequence of the growth of emerging countries, catalysed this crisis. The banking and financial crises are only the consequences of the cyclical decline of the rate of profit of the real economy since 1998.Since this date, the interest rates follow the rates of profit and the values of the shares, contrary to the previous period when the reduced rates doped the profits (The Glorious Thirty) and the high rates weakened them (The Years of Lead from 1975 till 1993). We so find again Adam Smith's theory where the long-term interest rate is determined by the rate of profit less a risk premium, enriched by that of the theory of the double speculation on the secondary financial markets of shares and bonds. But banks and monetary policies disrupt this game by the banking short rates: development of the criticism of Smith by Marx sending back to the keynesian monetary policy.